PENGGUNAAN MEDIA PEMBELAJARAN COLOR PAPER UNTUK MENINGKATKAN MINAT DAN KETERAMPILAN MENULIS PERMULAAN PADA MATA PELAJARAN BAHASA INDONESIA - Ayu Sri Rahayu; Kuswara; Nia Royani (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The background of this research is the low interest and early writing skills of students, especially in learning Indonesian. One of the factors that the reason why this happens is the lack of selection of learning media used to convey material that is still verbal. The problem that arises now is the low initial writing skills of students. Students tend to take for granted the material given by the teacher without responding in the form of opinions or rebuttals. To overcome this, researchers have a solution by applying color paper learning media. The purpose of this study was to describe the results of using color paper media in increasing students' interest and writing skills in starting students with living and non-living objects around me. Color paper media is a learning media made of paper that is attached with a sticky note which contains learning material. The research design used is the Kemmis and Mc Taggart spiral classroom action research (CAR) design. Based on the results of the study, it can be concluded that the color paper learning media can increase students' interest in learning and initial writing skills. It can be proven that the student's interest in learning has increased in each cycle. the results of the initial observation of the learning interest of grade I students at SD Negeri Bunter 1 in the Indonesian language subject with a total of 28 students, there were only 7 students in the